Imagery in Song Lyrics of Taylor Swift - Unpris Yastanti; Susilawati Susilawati (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The purposes of this research are to identify the kind of imagery in Taylor Swift song lyrics, how Taylor Swift describes imagery in her song lyrics, and dominant imagery in Taylor Swift song lyrics. This research limited to three songs in the “Reputation” album, those songs are Look What You Made Me Do, Delicate, Gorgeous. This research used a descriptive qualitative method to analyze the data. The results of this research indicate that (1) There are five kinds of imagery, they are visual imagery, auditory imagery, kinesthetic imagery, tactile imagery, and organic imagery in Taylor Swift song lyrics. There are nine visual imagery, one auditory imagery, three kinesthetic imagery, two tactile imagery, 19 organic imagery, and thus the writers found 34 imagery in three song lyrics of Taylor Swift. (2) Taylor Swift prefers to describe feelings, thought, and opinions into song lyrics, therefore the writers found a lot of organic imagery in the song lyrics. (3) There is 19 organic imagery in song lyrics, which is the dominant imagery in the song lyrics of Taylor Swift.